Avaliação dos aspectos epidemiológicos, clínicos e microscópicos da leucoplasia oral - Aguiar, Valdelya Nara Pereira (2022)
Oral Leukoplakia (OL) is a clinical term used to describe a predominantly white plaque of the oral mucosa, non-removable by scraping, which cannot be clinically classified into any other entity. It is considered the most prevalent potentially malignant disorder (PMD) in the population. Since “leukoplakia” is a clinical term, this lesion can be classified clinically according to its appearance and surface. From this, two main clinical subtypes were described: homogeneous OL (HOL) and non-homogeneous OL (NHOL). The relevance of OL lesions lies in their propensity to malignant transformation, which will depend on several factors. Thus, the aim of the present study is to evaluate the clinicopathological characteristics of OL, considering its two clinical subtypes, HOL and NHOL, in an attempt to identify parameters that contribute to the understanding and management appropriate for these injuries. A retrospective study was carried out, whose object of research was the medical records and histopathological reports of patients diagnosed with OL treated at the stomatology out patient clinics of Federal University of Ceará - UFC - Campus Sobral and Federal University of Rio Grande do Norte - UFRN, in the period between January 2007 to April 2021, totaling 109 cases. Results: 67 lesions (61.5%) were clinically classified as HOL and 42 were classified as NHOL (38.5%). In the HOL group, most patients were 40 years of age or older (86.6%) and were female (52.2%). The most affected locations were tongue (28.4%), buccal mucosa (28.4%) and alveolar ridge (22.4%). About 76.3% of the patients reported a history of current or previous smoking, 18.4% of these reported alcohol consumption and 5.3% of the patients had never had contact with tobacco nor reported alcohol consumption. In the NHOL group, 95.2% of individuals were 40 years of age or older and most were female (54.8%). Frequent locations were: Alveolar ridge (26.2%), tongue (21.4%) and buccal mucosa (21.4%). Current or previous smoking occurred in 53.3% of the cases, and alcohol consumption was reported in 10% of the individuals; 36.7% of patients had never had contact with tobacco or reported alcohol consumption. Histopathologically, based on the WHO grading system, most cases of HOL presented hyperkeratosis without epithelial dysplasia (ED) (43.3%) while for NHOL cases of mild epithelial dysplasia were prevalent (33.3%) and moderate (28.6%). In the Kujan binary grading system, a statistically significant difference was identified between the clinical subtypes, where cases classified as high risk were prevalent in the NHOL group (p<0.05).